2021
DOI: 10.3390/ma14040739
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Technological Capabilities for Forming Al-C-B System Coatings on Steel Surfaces by Electrospark Alloying Method

Abstract: In this paper, the possibility of applying the electrospark alloying (ESA) method to obtain boron-containing coatings characterised by increased hardness and wear resistance is considered. A new method for producing such coatings is proposed. The method consists in applying grease containing aluminium powder and amorphous boron to the surface to be treated and subsequently processing the obtained surface using the ESA method by a graphite electrode. The microstructural analysis of the Al-C-B coatings on steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
(32 reference statements)
0
9
0
1
Order By: Relevance
“…With periodic repetition of mechanical impact, the phase trajectory will turn into an open helical line. Using the phase plane method, assuming that one of the degrees of freedom has the highest relaxation rate, phase portraits of the boron-containing Al-C-B coating system were simulated in [26] and the diffusion process was studied. It was shown that near the stationary points in the phase portraits, either a slowing down of the evolution or a spiral twisting of part of the diffusion process is observed.…”
Section: The Phase Space Methods In the Study Of Strain-stress Fieldsmentioning
confidence: 99%
“…With periodic repetition of mechanical impact, the phase trajectory will turn into an open helical line. Using the phase plane method, assuming that one of the degrees of freedom has the highest relaxation rate, phase portraits of the boron-containing Al-C-B coating system were simulated in [26] and the diffusion process was studied. It was shown that near the stationary points in the phase portraits, either a slowing down of the evolution or a spiral twisting of part of the diffusion process is observed.…”
Section: The Phase Space Methods In the Study Of Strain-stress Fieldsmentioning
confidence: 99%
“…Відповідно до [66][67][68][69], залежно від конкретних умов леґування, застосовують додаткові технологічні прийоми. Наприклад, при леґуванні матеріялами, які «залипають» при зіткненні аноди з поверхнею, яку піддають леґуванню, що порушує частоту проходження імпульсів і збільшує нерівність поверхні, рекомендується попереднє короткочасне леґування поверхні іншим матеріялом на режимах з малою енергією імпульсів (так званих м'яких режимах) для утворення своєрідного перехідного тонкого шару.…”
Section: аналіза останніх досліджень і публікаційunclassified
“…This approach has broader implications beyond the specific case studied, as it can be applied to other laser processing scenarios where surface morphology plays a critical role [7][8][9]. Altering the characteristics of the surface layer is a commonly employed solution in various fields [10][11][12], and image analysis serves as a valuable diagnostic tool in this process [13][14][15]. These modifications are not only relevant to the energy sector [16], but also to hydraulic power systems [17,18] and the broader field of material engineering [19][20][21] and corrosion protection [22,23].…”
Section: Introductionmentioning
confidence: 99%